GE_GERICHTE P/14801/2002 vom 12. September 2007 - GE Cour de justice (2007)
ORDONNANCE DE RENVOI ; CLASSEMENT DE LA PROCÉDURE ; DÉLAI; NOTIFICATION ÉCRITE ; LIEU DE COMMISSION; COMPLICITÉ | CPP.192.1; CPP.198; CP.138; CP.146; CP.158; CP.25; CP.8